Childhood exposure to war and adult onset of cardiometabolic disorders among older Europeans. (September 2022) - Haas, Steven A.; Ramirez, Daniel
Abstract: Childhood exposure to contexts of war is a common occurrence among current and recent cohorts of children in various parts of the world. It was also common among older cohorts across Europe. Utilizing the Survey of Health, Ageing, and Retirement in Europe (SHARE) the present study links early life course residential histories with detailed information on the timing and location of hostilities during WWII to address three questions: 1) is childhood exposure to war associated with earlier onset of cardiometabolic disease (cardiovascular disease, hypertension, high cholesterol, and diabetes)? 2) did this additional risk vary depending on the timing of first exposure? 3) did this additional risk manifest via different life course pathways depending on exposure timing? Results demonstrate that exposure to war is associated with increased lifetime risk of cardiovascular disease, diabetes, high cholesterol, and hypertension and that this association is strongly concentrated among cohorts exposed in utero or during early childhood (e.g., before age 8). The results also suggest that the impact of war exposure on cardiometabolic disorders are likely to be direct, operating through latent biological processes rather than through childhood hardship, stunting of adult socioeconomic attainment, or elevated risk-taking behaviors. Highlights: Europeans exposed to war as children have earlier onset of cardiometabolic disease. The long-term impact of war varies by age at exposure. The impact of war is not mediated by subsequent the life course factors. Children exposed to war will carry the health impacts for the rest of their lives.